A high temperature resistant toughened adhesive and preparation method thereof
Through the preparation of modified toughening agent and combined with phenolic prepolymer, the problem of phenolic resin adhesives is solved, which significantly improves the stability and toughness of the glue layer and extends the service life of bamboo composite materials. .
Patent Information
- Application Number
- CN202410543851.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Phenolic resin adhesives are highly brittle in high temperature environments and are prone to cracks, affecting the mechanical properties and service life of bamboo composite materials. The existing toughening methods are costly or have poor toughening effects.
Modified toughening agent is prepared from materials such as tung oil, end epoxy silicone oil and 4-hydroxythiophenyl thiophenol. The chain compound is formed by ammonialysis and ultraviolet irradiation reaction, and combined with phenolic prepolymers to enhance the toughness of the adhesive and Thermal stability forms a high-temperature toughening adhesive.
It significantly improves the brittleness of the phenolic glue, improves the stability and aesthetics of the glue layer, enhances the toughness performance at high temperatures, avoids the occurrence of cracks, and extends the service life of bamboo composite materials.
Smart Images

Figure BDA0004821846980000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phenolic adhesives, and in particular, relates to a high temperature resistant toughened adhesive and a preparation method thereof. Background Art
[0002] Bamboo has a short growth period, fast growth, low planting cost, and can be cut and used every year after the forest is formed. In addition, bamboo is also wear-resistant, hard and dense, tough and strong. At the same time, bamboo also has special beautiful patterns and is widely used in furniture, flooring, interior decoration and handicrafts. Directly processing bamboo into products is extensive, inefficient, wasteful and limited in use. Bamboo composite materials, such as bamboo plywood, bamboo integrated materials, reconstructed bamboo, bamboo fiber composite materials, bamboo particleboard, etc., have more good properties and higher added value than single bamboo. Bamboo composite materials are usually processed into unit components through a series of treatments, applied with adhesives, and pressed by hot presses. In this process, adhesives are indispensable and are the key to ensuring the excellent physical and mechanical properties of bamboo composite materials. At present, phenolic resin adhesives are the most widely used adhesives for bamboo composite materials.
[0003] Phenolic resin adhesive is a synthetic high molecular polymer obtained by the reaction of phenol or substituted phenol with formaldehyde. It has the advantages of high bonding strength, good water and aging resistance, stable chemical properties, and wear resistance. However, the cured phenolic resin, due to its highly cross-linked aromatic ring network structure, makes the adhesive layer hard and brittle. When affected by the environment or external forces, it cannot effectively absorb or dissipate energy, and thus produces a large stress concentration at the bonding interface, which ultimately leads to cracking inside the adhesive layer or at the adhesive interface between the adhesive layer and the bamboo material. The generation of cracks not only affects the appearance, but also makes the bamboo composite material more susceptible to microbial invasion, resulting in mildew and decay, and reducing the mechanical properties and service life of bamboo products.
[0004] In the prior art, there are two main types of toughening methods for phenolic adhesives. One is chemical modification, which is to introduce toughening materials into the resin during the synthesis process to improve the toughness of the resin. This method has a stable toughening effect. However, the resin is used in large quantities as the main material of the adhesive, has high cost, and is limited in application. The second is physical toughening, which is to add a certain amount of toughening materials to the phenolic glue for toughening. This method is easy to operate and has high flexibility. For example, in the prior art, ethylene bisstearamide is used as a toughening agent, which can have a certain toughening effect on the phenolic glue. However, this type of small molecule toughening agent itself has insufficient thermal stability and is prone to free segregation under high temperature conditions, resulting in poor toughening effect. Summary of the invention
[0005] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a high temperature resistant toughened adhesive and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high temperature resistant toughening adhesive, comprising the following raw materials in parts by weight:
[0008] 100 parts of phenolic-based glue, 6.5-8 parts of modified toughening agent, 10-15 parts of lipophilic silica, 6-8 parts of diluent, 0.3-0.4 parts of leveling agent and 0.1-0.12 parts of antioxidant;
[0009] Furthermore, the diluent is selected from rosin water, which has good compatibility and dilution properties and is easy to evaporate and dry quickly.
[0010] Furthermore, the leveling agent is selected from an organosilicon leveling agent, which has good leveling properties and stable high temperature performance.
[0011] The modified toughening agent is prepared by the following method:
[0012] Step A1: tung oil, diethylenetriamine and toluene are mixed, nitrogen is introduced for protection, the temperature is raised to 80-90°C, stirring is applied at 60-80 rpm, sodium methoxide is added intermittently, and the total reaction time is controlled to be 3.5-4.5 hours. After the reaction is completed, the aqueous phase is washed away, and the toluene is evaporated in vacuo to obtain an aminolysis substrate;
[0013] Furthermore, the usage ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100 g: 0.4-0.5 mol: 1.8-2.1 g: 120-160 mL, and under the strong base action of sodium methoxide, excess diethylenetriamine is used to aminolyze the tung oil.
[0014] Step A2: The epoxy-terminated silicone oil, potassium hydroxide and dioxane are mixed, and nitrogen is passed through the mixture. Then, the ammonolysis substrate is added, and the temperature is raised to 75-85° C., and the mixture is stirred at 120-150 rpm for 1.5-2 hours. After the reaction is completed, the dioxane is evaporated in vacuo to obtain a toughened matrix;
[0015] Furthermore, the usage ratio of the ammonolysis substrate, the terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:160-240g:2-2.5g:80-110mL, and the active amino group of the ammonolysis substrate and the epoxy group of the terminal epoxy silicone oil are ring-opened to graft the ammonolysis substrate to the end of the silicone chain.
[0016] Furthermore, the epoxy-terminated silicone oil is selected from small molecular weight low viscosity silicone oil, and the room temperature viscosity is not higher than 100 mm 2 / s, the dispersion and toughening effect is better.
[0017] Step A3: 4-hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, ammonia water was added to adjust the pH value of the mixture to 8-9, the mixture was heated to 70-80°C, stirred and refluxed for 1.3-1.7h, then cooled to a constant temperature of 35-45°C, a toughening matrix was added, and 300-400W / m 2 The reaction was continued under ultraviolet irradiation and stirring for 2-3 hours. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent.
[0018] Furthermore, the dosage ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol is 0.1 mol: 0.22-0.25 mol: 45-52 g: 0.3-0.5 g: 90-130 mL, and formaldehyde reacts with 4-hydroxythiophenol to form a phenolic prepolymer containing a thiol group, which is then click-added with the unsaturated structure in the toughening matrix molecule under the promotion of ultraviolet radiation and introduced into the end of the toughening matrix.
[0019] A preparation method of a high temperature resistant toughened adhesive comprises the following specific operations: premixing a modified toughening agent, a leveling agent, an antioxidant and a diluent, adding phenolic base glue and mixing evenly, then adding oleophilic silica and mixing, and vacuum degassing to obtain the high temperature resistant toughened adhesive.
[0020] Beneficial effects of the present invention:
[0021] The adhesive disclosed by the invention uses traditional phenolic adhesive as a base material, and significantly improves its brittleness by compounding a self-made modified toughening agent. In particular, under high temperature working conditions, the adhesive layer has high stability and is not easy to produce cracks that affect bonding and aesthetics. The modified toughening agent uses biomass tung oil as a raw material, and is subjected to aminolysis by excessive diethylenetriamine under the strong base action of sodium methoxide to form an aminolysis substrate containing active amino groups, and then a low-molecular-weight terminal epoxy silicone oil and its amino group are ring-opened to form a chain compound with a silicon chain in the middle and an aminolysis substrate at the end, i.e., a toughening matrix. Finally, formaldehyde and 4-hydroxythiophenol are reacted to form a phenolic prepolymer containing a mercapto group, and then, under the promotion of ultraviolet radiation, the phenolic prepolymer reacts with the residual unsaturated fatty acids in the toughening matrix molecules caused by the aminolysis of tung oil. The saturated structure is click-added and introduced into the end of the toughening matrix; the silicon chain in the modified toughening agent molecule is interspersed in the phenolic cross-linked network, which greatly weakens the force between the molecular chains and plays a strong toughening effect, and the silicon chain has high thermal stability, and can maintain good structural stability during the high-temperature curing and high-temperature service of the phenolic glue; the phenolic prepolymer at its end plays a similar compatible modification role, so that the chain-like modified toughening agent molecules can be stretched and dispersed in the phenolic glue, and its macromolecular chain structure makes it difficult to free segregate under high temperature environment. In addition, the phenolic prepolymer at the end can participate in the cross-linking of the substrate during the curing process, forming a toughness hub with end cross-linking and middle toughening, which effectively prevents the adhesive layer from cracking at high temperature. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1, preparation of high temperature resistant toughened adhesive, specifically as follows:
[0024] 1) Preparation of modified toughening agent
[0025] Step A1: tung oil, diethylenetriamine and toluene are mixed, wherein the tung oil comes from the refined tung oil of Nanjing Nature Fine Chemical Co., Ltd., nitrogen is introduced for protection, the temperature is raised to 90°C, stirring is applied at 80rpm, and sodium methoxide is divided into three parts by mass, and added intermittently for 30 minutes. After the addition is complete, the stirring reaction is continued at a constant temperature, and the total addition reaction time of the tung oil is controlled to be 3.5 hours. Among them, the amount ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100g:0.5mol:2.1g:160mL. After the reaction is completed, the aqueous phase is washed with water to remove the aqueous phase, and the toluene is evaporated in vacuo to obtain an aminolysis substrate.
[0026] Step A2: Take end-epoxy silicone oil, potassium hydroxide and dioxane and mix them. The end-epoxy silicone oil is from Shin-Etsu X-22-163B silicone oil, and the room temperature viscosity is about 60 mm 2 / s, under nitrogen protection, add the ammonolysis substrate, raise the temperature to 85°C, and stir at 150rpm to react for 1.5h, wherein the amount ratio of the ammonolysis substrate, terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:240g:2.5g:110mL. After the reaction, dioxane is evaporated in vacuum to obtain a toughened matrix.
[0027] Step A3: 4-Hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, industrial ammonia was added to adjust the pH value of the mixture to 8, the mixture was heated to 80°C and stirred under reflux for 1.3h, then cooled to 45°C and kept at a constant temperature, and a toughening matrix was added, supplemented with 400W / m 2 The reaction was continued under ultraviolet irradiation and stirring for 2 hours, wherein the amount ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol was 0.1 mol: 0.25 mol: 52 g: 0.5 g: 130 mL. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent.
[0028] 2) Prepare adhesive
[0029] Preparation of materials: raw materials are taken according to weight parts, 100 parts of phenolic glue, all of which are phenolic glue E0 from Dalian Jinxin Chemical Co., Ltd.; 6.5 parts of modified toughening agent, which is homemade in this embodiment; 15 parts of lipophilic silica, all of which are VK-SP30S products from Xuancheng Jingrui New Materials Co., Ltd.; 6 parts of diluent, all of which are industrial-grade rosin water provided by Hubei Exiang Chemical Co., Ltd.; 0.3 parts of leveling agent, all of which are AKN-1170 type silicone leveling agent from Foshan Qianyou Chemical Co., Ltd.; 0.12 parts of antioxidant, all of which are antioxidant 1010 and antioxidant 168 compounded in equal quality;
[0030] Glue preparation: Add modified toughening agent, leveling agent, antioxidant and diluent and premix at 300 rpm for 10 minutes, then add phenolic base glue and mix at 60 rpm for 30 minutes, then add oleophilic silica and mix at 120 rpm for 20 minutes, and vacuum degassing for 30 minutes to obtain high temperature resistant toughened adhesive.
[0031] Example 2, preparation of high temperature resistant toughened adhesive, specifically as follows:
[0032] 1) Preparation of modified toughening agent
[0033] Step A1: tung oil, diethylenetriamine and toluene are mixed, wherein the tung oil comes from the refined tung oil of Nanjing Nature Fine Chemical Co., Ltd., nitrogen is introduced for protection, the temperature is raised to 80°C, stirring is applied at 60rpm, and sodium methoxide is divided into three parts by mass, and added intermittently for 40 minutes. After the addition is complete, the reaction is continued by stirring at a constant temperature, and the total addition reaction time of the tung oil is controlled to be 4.5 hours. The amount ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100g:0.4mol:1.8g:120mL. After the reaction is completed, the aqueous phase is washed with water to remove the aqueous phase, and the toluene is evaporated in vacuo to obtain an aminolysis substrate.
[0034] Step A2: Take end-epoxy silicone oil, potassium hydroxide and dioxane and mix them. The end-epoxy silicone oil is from Shin-Etsu X-22-163A silicone oil, and the room temperature viscosity is about 30 mm 2 / s, under nitrogen protection, add the ammonolysis substrate, raise the temperature to 75°C, and stir at 120rpm to react for 2h, wherein the amount ratio of the ammonolysis substrate, terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:160g:2g:80mL, and after the reaction is completed, dioxane is evaporated in vacuum to obtain a toughened matrix.
[0035] Step A3: 4-Hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, industrial ammonia was added to adjust the pH value of the mixture to 9, the mixture was heated to 70°C and stirred under reflux for 1.7h, then cooled to a constant temperature of 35°C, a toughening matrix was added, and 300W / m 2The reaction was continued under ultraviolet irradiation and stirring for 3 hours, wherein the amount ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol was 0.1 mol: 0.22 mol: 45 g: 0.3 g: 90 mL. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent.
[0036] 2) Prepare adhesive
[0037] Preparation of materials: raw materials are taken according to weight parts, 100 parts of phenolic glue, all of which are phenolic glue E0 from Dalian Jinxin Chemical Co., Ltd.; 7.2 parts of modified toughening agent, which is homemade in this embodiment; 10 parts of lipophilic silica, all of which are VK-SP30S products from Xuancheng Jingrui New Materials Co., Ltd.; 7 parts of diluent, all of which are industrial-grade rosin water provided by Hubei Exiang Chemical Co., Ltd.; 0.3 parts of leveling agent, all of which are AKN-1170 type silicone leveling agent from Foshan Qianyou Chemical Co., Ltd.; 0.11 parts of antioxidant, all of which are antioxidant 1010 and antioxidant 168 compounded in equal quality;
[0038] Glue preparation: Add modified toughening agent, leveling agent, antioxidant and diluent and premix at 300 rpm for 10 minutes, then add phenolic base glue and mix at 60 rpm for 30 minutes, then add oleophilic silica and mix at 120 rpm for 20 minutes, and vacuum degassing for 30 minutes to obtain high temperature resistant toughened adhesive.
[0039] Example 3, preparation of high temperature resistant toughened adhesive, as follows:
[0040] 1) Preparation of modified toughening agent
[0041] Step A1: tung oil, diethylenetriamine and toluene are mixed, wherein the tung oil comes from the refined tung oil of Nanjing Nature Fine Chemical Co., Ltd., nitrogen is introduced for protection, the temperature is raised to 85°C, stirring is applied at 70rpm, and sodium methoxide is divided into three parts by mass, and added intermittently for 35 minutes. After the addition is complete, the constant temperature stirring reaction is continued, and the total addition reaction time of the tung oil is controlled to be 4.2 hours. Among them, the amount ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100g:0.45mol:1.8g:150mL. After the reaction is completed, the aqueous phase is washed with water to remove the aqueous phase, and the toluene is evaporated in vacuo to obtain an aminolysis substrate.
[0042] Step A2: Take end-epoxy silicone oil, potassium hydroxide and dioxane and mix them. The end-epoxy silicone oil is from Shin-Etsu X-22-163B silicone oil, and the room temperature viscosity is about 60 mm 2 / s, under nitrogen protection, add the ammonolysis substrate, raise the temperature to 82°C, and stir at 150rpm to react for 1.8h, wherein the amount ratio of the ammonolysis substrate, terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:220g:2.2g:100mL, and after the reaction is completed, dioxane is evaporated in vacuum to obtain a toughened matrix.
[0043] Step A3: 4-Hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, industrial ammonia was added to adjust the pH value of the mixture to 8, the mixture was heated to 75°C and stirred under reflux for 1.6h, then cooled to 40°C and kept at a constant temperature, and a toughening matrix was added, supplemented with 360W / m 2 The reaction was continued under ultraviolet irradiation with stirring for 2.5 hours, wherein the amount ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol was 0.1 mol: 0.23 mol: 50 g: 0.4 g: 110 mL. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent.
[0044] 2) Prepare adhesive
[0045] Preparation of materials: raw materials are taken according to weight parts, 100 parts of phenolic glue, all of which are phenolic glue E0 from Dalian Jinxin Chemical Co., Ltd.; 7.5 parts of modified toughening agent, which is homemade in this embodiment; 13 parts of lipophilic silica, all of which are VK-SP30S products from Xuancheng Jingrui New Materials Co., Ltd.; 8 parts of diluent, all of which are industrial-grade rosin water provided by Hubei Exiang Chemical Co., Ltd.; 0.4 parts of leveling agent, all of which are AKN-1170 type silicone leveling agent from Foshan Qianyou Chemical Co., Ltd.; 0.11 parts of antioxidant, all of which are antioxidant 1010 and antioxidant 168 compounded in equal quality;
[0046] Glue preparation: Add modified toughening agent, leveling agent, antioxidant and diluent and premix at 300 rpm for 10 minutes, then add phenolic base glue and mix at 60 rpm for 30 minutes, then add oleophilic silica and mix at 120 rpm for 20 minutes, and vacuum degassing for 30 minutes to obtain high temperature resistant toughened adhesive.
[0047] Example 4, preparation of high temperature resistant toughened adhesive, specifically as follows:
[0048] 1) Preparation of modified toughening agent
[0049] Step A1: tung oil, diethylenetriamine and toluene are mixed, wherein the tung oil comes from the refined tung oil of Nanjing Nature Fine Chemical Co., Ltd., nitrogen is introduced for protection, the temperature is raised to 85°C, stirring is applied at 80rpm, and sodium methoxide is divided into three parts by mass, and added intermittently for 35 minutes. After the addition is complete, the reaction is continued by constant temperature stirring, and the total addition reaction time of the tung oil is controlled to be 4 hours. The amount ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100g:0.42mol:2.1g:150mL. After the reaction is completed, the aqueous phase is washed away with water, and the toluene is evaporated in vacuo to obtain an aminolysis substrate.
[0050] Step A2: Take end-epoxy silicone oil, potassium hydroxide and dioxane and mix them. The end-epoxy silicone oil is from Shin-Etsu X-22-163A silicone oil, and the room temperature viscosity is about 30 mm 2 / s, under nitrogen protection, add the ammonolysis substrate, raise the temperature to 82°C, and stir at 150rpm to react for 1.5-2h, wherein the amount ratio of the ammonolysis substrate, terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:2g:2.3g:100mL, and after the reaction is completed, dioxane is evaporated in vacuum to obtain a toughened matrix.
[0051] Step A3: 4-Hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, industrial ammonia was added to adjust the pH value of the mixture to 9, the mixture was heated to 75°C, stirred and refluxed for 1.5h, then cooled to 42°C and kept at a constant temperature, and a toughening matrix was added, supplemented with 320W / m 2 The reaction was continued under ultraviolet irradiation with stirring for 2.5 hours, wherein the amount ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol was 0.1 mol: 0.23 mol: 48 g: 0.4 g: 110 mL. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent.
[0052] 2) Prepare adhesive
[0053] Preparation: Take the raw materials according to weight parts, 100 parts of phenolic glue, all of which are phenolic glue E0 from Dalian Jinxin Chemical Co., Ltd.; 8 parts of modified toughening agent, which is homemade in this embodiment; 11 parts of oleophilic silica, all of which are VK-SP30S products from Xuancheng Jingrui New Materials Co., Ltd.; 8 parts of diluent, all of which are industrial-grade rosin water provided by Hubei Exiang Chemical Co., Ltd.; 0.4 parts of leveling agent, all of which are AKN-1170 type silicone leveling agent from Foshan Qianyou Chemical Co., Ltd.; 0.1 parts of antioxidant, all of which are antioxidant 1010 and antioxidant 168 compounded in equal quality;
[0054] Glue preparation: Add modified toughening agent, leveling agent, antioxidant and diluent and premix at 300 rpm for 10 minutes, then add phenolic base glue and mix at 60 rpm for 30 minutes, then add oleophilic silica and mix at 120 rpm for 20 minutes, and vacuum degassing for 30 minutes to obtain high temperature resistant toughened adhesive.
[0055] Comparative Example, referring to the prior art, ethylene bis stearamide is used for toughening, as follows:
[0056] Preparation: Take the raw materials according to weight parts, 100 parts of phenolic glue, all of which are phenolic glue E0 from Dalian Jinxin Chemical Co., Ltd.; 7.4 parts of ethylene bis stearic acid amide, which is homemade in this embodiment; 12 parts of lipophilic silica, all of which are VK-SP30S products from Xuancheng Jingrui New Materials Co., Ltd.; 8 parts of diluent, all of which are industrial-grade rosin water provided by Hubei Exiang Chemical Co., Ltd.; 0.4 parts of leveling agent, all of which are AKN-1170 type silicone leveling agent from Foshan Qianyou Chemical Co., Ltd.; 0.1 parts of antioxidant, all of which are antioxidant 1010 and antioxidant 168 compounded in equal quality;
[0057] Glue preparation: Add modified toughening agent, leveling agent, antioxidant and diluent and premix at 300 rpm for 10 minutes, then add phenolic base glue and mix at 60 rpm for 30 minutes, then add oleophilic silica and mix at 120 rpm for 20 minutes, and vacuum degassing for 30 minutes to obtain high temperature resistant toughened adhesive.
[0058] In order to verify the bonding performance of the above-obtained adhesive on bamboo, peeled yellow bamboo sheets were taken as samples, and glue was applied on one side of the bamboo sheets, and the glue application amount was controlled to be 100g / m 2 , the glued surfaces were bonded and naturally bonded under 0.2MPa air pressure clamp for 30 minutes, then transferred to the hot press, the temperature was controlled at 150±5℃, the pressure was 1.2±0.05MPa, after hot pressing for 10 minutes, the materials were cooled, the excess glue was scraped off, and the materials were naturally left to stand for 24 hours to obtain the bonded samples, and the bonding strength test was carried out according to EN 302-1:2013 standard;
[0059] In order to verify the toughness of the adhesive obtained above after curing, the adhesive was injected into the mold cavity coated with a release agent, and the curing was controlled at 150±5℃ for 10 minutes. After standing naturally for 24 hours, the film was demoulded to obtain the film, and the impact performance test was carried out according to GB / T1043.1-2008 standard;
[0060] To verify the surface state of the adhesive after curing, the adhesive was applied on the surface of the bamboo strips, and the amount of adhesive applied was controlled to be 120 g / m 2 , put it in an oven at 150±5℃ for 15min, let it stand for 24h after natural cooling to simulate the initial curing state,
[0061] An ultra-depth-of-field three-dimensional microscope was used to observe the state of the adhesive layer and statistically calculate the crack state. At the same time, the cured samples were baked at 200°C and 250°C for 1 hour, respectively, and naturally cooled to room temperature to simulate service conditions under high temperature, and the crack state was observed and calculated again.
[0062] The specific test data is shown in Table 1:
[0063] Table 1
[0064]
[0065] From the test results in Table 1, it can be seen that the bonding strength of the adhesive prepared in the embodiment to the bamboo yellow sheet is 14.25-15.19 MPa, which is slightly higher than 13.84 MPa of the comparative example. After analysis, it should be because the added free ethylene bis stearic acid amide destroys the continuity of the adhesive, resulting in a decrease in cohesion and a slightly lower bonding strength; the impact strength of the film in the embodiment is 1.36-1.49 J / cm 2 , similar to the comparative example, and have good toughening effect compared with pure phenolic glue; in the high-temperature service condition test, within the temperature of 200°C, the crack width of the embodiment is lower than that of the comparative example. When the temperature reaches 250°C, the cracks of the comparative example are serious, with an average width of 66.27μm, and visible crack lines appear in the glue layer, seriously affecting the appearance.
[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0067] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high temperature resistant toughening adhesive, characterized in that: The composition comprises, by weight: 100 parts of phenolic rubber, 6.5-8 parts of modified toughening agent, 10-15 parts of lipophilic silica, 6-8 parts of diluent, 0.3-0.4 parts of leveling agent and 0.1-0.12 parts of antioxidant; The modified toughening agent is prepared by the following method: Step A1: tung oil, diethylenetriamine and toluene are mixed, nitrogen is introduced for protection, the temperature is raised to 80-90°C, sodium methoxide is added intermittently while stirring, and the total reaction time is controlled to be 3.5-4.5h. After the reaction is completed, the aqueous phase is washed and removed, and toluene is evaporated in vacuo to obtain an aminolysis substrate, wherein the amount ratio of tung oil, diethylenetriamine, sodium methoxide and toluene is 100g: 0.4-0.5mol: 1.8-2.1g: 120-160mL; Step A2: Mix terminal epoxy silicone oil, potassium hydroxide and dioxane, and then add the ammonolysis substrate under nitrogen protection, raise the temperature to 75-85°C, stir and react for 1.5-2h, and evaporate the dioxane in vacuum after the reaction to obtain a toughened matrix, wherein the amount ratio of the ammonolysis substrate, terminal epoxy silicone oil, potassium hydroxide and dioxane is 10g:160-240g:2-2.5g:80-110mL; Step A3: 4-hydroxythiophenol, formaldehyde aqueous solution, o-cresol and ethanol were mixed, ammonia water was added to adjust the pH value of the mixture to 8-9, the mixture was heated to 70-80°C, stirred and refluxed for 1.3-1.7h, then cooled to a constant temperature of 35-45°C, a toughening matrix was added, and 300-400W / m 2 The reaction was continued under ultraviolet irradiation and stirring for 2-3 hours. After the reaction was completed, ethanol and water were evaporated in vacuo to obtain a modified toughening agent, wherein the amount ratio of 4-hydroxythiophenol, formaldehyde, toughening matrix, o-cresol and ethanol was 0.1 mol: 0.22-0.25 mol: 45-52 g: 0.3-0.5 g: 90-130 mL.
2. A high temperature resistant toughened adhesive according to claim 1, characterized in that: The room temperature viscosity of the epoxy silicone oil is not higher than 100mm 2 / s.
3. The high temperature resistant toughened adhesive according to claim 1, characterized in that: The diluent is selected from rosin water.
4. The high temperature resistant toughened adhesive according to claim 1, characterized in that: The leveling agent is selected from silicone leveling agents.
5. A high temperature resistant toughened adhesive according to any one of claims 1 to 4, characterized in that: The specific operation is: premix the modified toughening agent, leveling agent, antioxidant and diluent, add phenolic base glue and mix well, then add oleophilic silica and mix, and obtain the high temperature resistant toughened adhesive after vacuum degassing.
